2021
DOI: 10.1021/acs.jpcb.1c03745
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry Breaking in an Excited Quadrupolar Acridine-Dione Derivative Driven by Hydrogen Bonding

Abstract: acridine-1.9(2H,5H)dion) with quadrupolar motif has been synthesized and its stationary and transient spectra have been measured. Stationary absorption and fluorescence spectra as well as nonstationary spectra show no signs of symmetry breaking (SB) in aprotic solvents, even of high polarity. The specific features of SB are revealed in alcohol solvents through a considerable red shift of stationary fluorescence spectra and the appearance of a new excited state absorption band in transient absorption spectra. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Let us start with a qualitative discussion. First, the reduction in the square of the transition dipole moment with increasing λ or , pictured in Figure , fully agrees with the experimentally observed decrease in the emission moment with an increase in the solvent polarity. Second, the scale of the predicted changes in the transition dipole moment due to symmetry breaking is close to that detected in the experiments (a decrease in the emission dipole moment by about 20% and 30% was reported in refs and and in ref , respectively). Third, the observed reduction in the instantaneous emission dipole moments in polar solvents occurring in a time interval of several picoseconds , also agrees with model considered here.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Let us start with a qualitative discussion. First, the reduction in the square of the transition dipole moment with increasing λ or , pictured in Figure , fully agrees with the experimentally observed decrease in the emission moment with an increase in the solvent polarity. Second, the scale of the predicted changes in the transition dipole moment due to symmetry breaking is close to that detected in the experiments (a decrease in the emission dipole moment by about 20% and 30% was reported in refs and and in ref , respectively). Third, the observed reduction in the instantaneous emission dipole moments in polar solvents occurring in a time interval of several picoseconds , also agrees with model considered here.…”
Section: Resultssupporting
confidence: 86%
“…So, the effect of SB on the emission transition dipole moment is expected to be significant only in the dyes with strong SB degree, when the excitation is practically fully localized on one branch of the dye. It has been shown that the formation of H-bonds between solvent molecules and the dye can greatly increase the degree of SB. ,,, Indeed, an effect of SB on the transition dipole moment of a larger scale (0.21) was found with a dye in protic solvents, where a hydrogen bond is likely to trigger SB …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, the attempts to visualize ES-SB using UV–vis TA were generally not really successful because no clear spectral signature could be detected. , The spectral dynamics observed in the UV–vis region is often dominated by the red shift of the stimulated emission band. This shift together with the frequent overlap of the stimulated emission band with positive ESA features seriously complicates the determination of its area and, thus, the detection of ES-SB.…”
Section: Looking At Symmetry-forbidden Vibrational Transitionsmentioning
confidence: 99%